Genetic, biological and epidemiological study on a cluster of H9N2 avian influenza virus infections among chickens, a pet cat, and humans at a backyard farm in Guangxi, China. Issue 1 (31st December 2023) - Yang, Jing; Yan, Jianhua; Zhang, Cheng; Li, Shanqin; Yuan, Manhua; Zhang, Chunge; Shen, Chenguang; Yang, Yang; Fu, Lifeng; Xu, Guanlong; Shi, Weifeng; Ma, Zhenghai; et al.
ABSTRACT: During an investigation in October 2018, two people with diarrhoea, mild abdominal pain, and mild arthralgia symptoms in Guangxi, China, were identified as infected by H9N2 avian influenza virus (AIV). Four H9N2 AIVs were isolated from one of two patients, a pet cat, and a dead chicken (two respective isolates from its lung and kidney tissues) bred by the patients at a backyard farm. Epidemiological investigation indicated that the newly bought chicken died first, and clinical syndromes appeared subsequently in the two owners and one cat. Furthermore, the two individuals possessed high H9N2-specific hemagglutination inhibition and microneutralization antibodies. Shared nucleotide sequence identity (99.9% – 100%) for all genes was detected in the four H9N2 isolates, and hemagglutinin (HA) T138A located on the receptor binding domain (RBD), resulted from nucleotide polymorphisms that were exclusively found in the isolate from the female patient. Moreover, HA K137N on the RBD was found in isolates from these three host species. Importantly, these four H9N2 isolates presented an exclusive binding preference for the human-type receptor (α2-6-SA), and could replicate and cause pathological changes in mice. Phylogenetic analyses showed that these four isolates clustered together and belonged to clade C1.2, lineage Y280. In addition, H9N2 viruses of human origin are genetically divergent and interspersed with the widespread poultry-origin H9N2 AIVs. All these results indicate a high risk of H9N2 AIVs in public health, and effective prevention and control measures against H9N2 AIVs should be considered and performed for both animal and human health.